ระบบสนับสนุนการให้คำปรึกษาวิชาการโดยใช้กูเกิลแอพเอนจิน - กนกวรรณ มาลังค์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study presents the Academic Advisory Support System Using Google App Engine (AASS). The purposes of this study is to develop the academic advising system in a form of web application using Google App Engine platform, Gmail and Google Calendar which can facilitate the software development process based on cloud computing architecture. Another purpose is to improve the academic advising process in College of Arts, Media and Technology, Chiang Mai University through the effective outcomes. Therefore, the developed system can be applied as a tool or a channel for exchanging all useful information among students, lecturers, and other academic staff. The development of AASS consists of 5 major components; Membership Directory, Office Hours, Appointment and Email Alert, Academic Advising, and Summary and Reporting. The AASS implementation process relied on the Iterative and Incremental model in which the whole system are divided into five phases based on five major components. At each phase, SDLC operations (requirement, design, develop, test and review) are executed. Moreover, the development of AASS has followed the software standard and guidelines for very small entities (ISO/IEC 29110) in order to ensure the perfective software development process, and improve software product's quality. The results from evaluating user’s satisfaction in the real system environment found that it was good on average. Most of the users were satisfied with the system because AASS provides more flexible to access to the advising process and all related data over the Internet without any locations and time-of-use restrictions. In management dimension, educational institute can analyze academic advising data for making decisions. Using AASS can reduce growing expenses for intensive-labor service and overhead costs. In software development dimension, the utilization of Google Cloud Platform in combining with Google Application can reduce the complexity during the development process. With these tools, data storage and maintenance resources are not necessary to be concerned. Therefore, software development team members can get more convenience for developing software application to satisfy the user requests.